Flipping Classrooms in a School of Public Health - Howard, Steven W.; Scharff, Darcell P.; Loux, Travis M. (Frontiers in Public Health, 2017)
Alternative course formats are gaining increasing attention in higher education. The literature provides a number of examples and studies of flipped classrooms in the medical sciences and liberal arts and sciences. However, fewer than five papers on flipped classes in graduate public health courses have been published, and none in health management. Because graduate public health education is competency based, it seems that a flipped approach with its applied nature would be an appropriate form of teaching public health courses. This paper describes three successfully flipped courses taught in a school of public health. We provide a rationale for flipping, description of each course and lessons learned. Once some of the challenges are overcome, we believe flipping courses can provide an alternative approach that enhances active learning in applied, public health and health management courses.